MBRS-30. TORC1/2 INHIBITION SENSITIZES MYC-DRIVEN MEDULLOBLASTOMA CELLS TO CARBOPLATIN CHEMOTHERAPY. Issue 2 (22nd June 2018) - Maynard, Rachael; Hanaford, Allison; Poore, Bradley; Rubens, Jeffrey; Archer, Tenley; Tamayo, Pablo; Pomeroy, Scott; Eberhart, Charles; Raabe, Eric
Abstract: Medulloblastoma is the most common malignant pediatric brain tumor. Tumors having high levels of c-MYC have the worst clinical prognosis, with only a minority of patients surviving. We performed an in silico analysis of human stem cell model of medulloblastoma, which predicted mTOR inhibitors as a potential therapeutic agent. We hypothesized that the dual TORC1/1 inhibitor TAK228 would have activity against MYC-driven medulloblastoma. We tested this hypothesis using the MYC-amplified medulloblastoma cell lines D425 and D283. We determined that TAK228 was effective in inhibiting both mTORC1/2 in D425 at concentrations of 20nM as measured by western blots showing decreased p-S6 (90% decrease) and p-AKT473 (70% decrease) expression. We found that treatment with TAK228 decreases cell growth at concentrations of 20nM (D425 p<0.005 vs vehicle, D283 p<0.0005 vs vehicle) and induces apoptosis as measured by cleaved caspase 3 staining and increased expression of cleaved PARP (D425 p<0.05 vs vehicle, D283 p<0.0005 vs vehicle). Because mTOR inhibition can suppress glutathione production, and glutathione is required to detoxify platinum containing chemotherapy, we hypothesized that TAK228 would cooperate with the platinum containing chemotherapy, carboplatin. TAK228 in combination with carboplatin inhibits growth (D425 p<0.05 vs vehicle, D283 p<0.05 vs vehicle) and induces apoptosis as measured by cleaved PARP expression (7-fold increase in combination versus vehicle). In vivo testing is currently underway to determine the survival benefit of TAK228 in combination with carboplatin. TAK228 is effective at inhibiting growth and inducing apoptosis in high-MYC medulloblastoma cell lines and shows combinatorial efficacy with carboplatin.